"Morality and authority in existential praxis" - Praeg, Leonhard (Rhodes University, Faculty of Education, Department of Education, 2006)
In this study I am concerned with understanding how the emergence of participatory or, broadly understood, existential approaches to education has shifted the nature of the student/lecturer relationship. Historically, the difference was represented through the in loco parentis trope which contains implicit understandings as to the nature of the lecturer's authority and the ethical parameters of the relationship. With the emergence of more participatory approaches this relationship and its constitutive elements have to be re-imagined. In the first chapter I place this enquiry in the contemporary context in which the very identity of the university is changing as a result of massification and the accountability regime. In the second chapter I look at bell hooks' pedagogy as an example of such a participatory approach to education at higher education institutions. I describe her practice as a deconstructive pedagogy that is as powerful as it is because of the operation of a difference constitutive of it. In the third chapter I ask whether representing this difference in terms of the pre-modern master/apprentice offers a useful response to the questions raised by an existential praxis.
Keywords: Hooks, Bell; Teacher-student relationships; Education, Higher; Knowledge, Sociology of; Universities and colleges; Educational change; College teaching; Philosophy